Predictors of complications associated with extracorporeal membrane oxygenation - Nakasato,Gislaine Rodrigues (2020)
ABSTRACT Objectives: to identify in the literature, the predictors of ECMO complications in adult patients. Methods: integrative review of literature, including articles in Portuguese, English and Spanish published from 2014 to 2018 in five databases. Included articles which analyzed the predictive factors of ECMO complications in adult patients using multivariate analysis. Results: a total of 1629 articles were identified, of which 19 were included. Nineteen predictors were identified for neurological complications (e.g., post-ECMO hypoglycemia), seven for bleeding complications (e.g., fungal pneumonia), four for infections complications (e.g., preoperative creatinine level), three for kidney complications (e.g., the length of ICU stay> 20 days) and a combination of factors for mechanical complications (e.g., median flow). Conclusions: different predictors were identified to ECMO complications. The knowledge of these predictors enables the individualized targeting of preventive interventions by multidisciplinary team for modifiable factors, as well as intensification of monitoring for early recognition of non-modifiable factors.